2019
DOI: 10.1080/0142159x.2019.1665633
|View full text |Cite
|
Sign up to set email alerts
|

Realist approach to evaluating an interprofessional education program for medical students in clinical practice at a community hospital

Abstract: Introduction: We examined the interrelationships between context, mechanism, and outcome using a realist approach following the introduction of interprofessional education (IPE) to clinical practice for medical students in the community. Methods: Through participant observation and interviews, a working hypothesis was developed. To evaluate IPE in clinical practice, medical students' reports were thematically analyzed, and configuration on contexts, mechanisms, and outcomes were identified using a realist appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…25,26 Moreover, CBIPE helps stimulate social accountability in health profession students. 27 Various approaches to CBIPE have been previously reported such as learning in rural and primary healthcare settings, 24,28,29 community-based learning within broader community context 16,22,30 and for specific community context; the commonly used model of CBIPE in the western countries. 21,[31][32][33][34][35] The nature of interprofessional learning activities is mainly to provide healthcare services primary healthcare setting, not in the community.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Moreover, CBIPE helps stimulate social accountability in health profession students. 27 Various approaches to CBIPE have been previously reported such as learning in rural and primary healthcare settings, 24,28,29 community-based learning within broader community context 16,22,30 and for specific community context; the commonly used model of CBIPE in the western countries. 21,[31][32][33][34][35] The nature of interprofessional learning activities is mainly to provide healthcare services primary healthcare setting, not in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The participants strongly emphasized that current general medicine education at universities is poor and insufficient. Japan and other countries have reported that students can learn more regarding primary care and multiprofessional cooperation in community hospital training; furthermore, they primarily learn concerning rare diseases (by organ) during university training [26,27]. The effectiveness of community-based general medicine education has been demonstrated [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Tasks should always be adequate for MC settings and non-interrruptive. Students should develop communicative skills in radiology (Slanetz, 2011;Rahim & Ros, 2016), and for future clinical practice in all medical disciplines (Gunderman et al, 2003;ESR, 2017;Haruta & Yamamoto, 2020). Such self-organised and responsible learning will prepare medical students completing their electives for future clinical practice within and outside of radiology (Schüßler, 2012;Arnold, 2015).…”
Section: Proactive Learningmentioning
confidence: 99%
“…This way students would actively contribute to educational goals of MCs (O'Brien et al, 2017;Goulao, 2020). Moreover, students get to train communicative skills in medical contexts evolving around diagnostic and therapeutic decisions (Gunderman et al, 2003;Rahim & Ros, 2016;ESR, 2017;Haruta & Yamamoto, 2020) − skills imperative for their upcoming residency. Instead of expecting medical doctors to deliver on additional teaching when deciding on patient diagnoses and therapies, students can be involved in multidisciplinary communication and interaction.…”
Section: 2teaching and Learning Processesmentioning
confidence: 99%